Synthesis Of Asymmetric Polyetherimide Membrane For co2 n2 Separation - Olatunji_, Salaudeen Yusuf (2017)
The climate change becomes the global challenges due to the increasing earth’s surface temperature. This phenomenon was aggravated by the expansion of industrial activities due to the increasing emissions of the greenhouse gas mainly CO2. This makes the separation of CO2 from flue gas attracted research interest due to increasing demand for energy and the need for more energy efficient and environmental friendly gas separation technique. Most of the flue gases are coproduced with CO2 which needs to be removed in order to have a clean environment. Dry-wet phase inversion process is one of the techniques that were adopted in this work to further improve the membrane performance. The adopted technique used to performed the dry-wet phase inversion is to have a dense asymmetric and a less pores at the surface of the membrane to allow a more selective CO2. The use of higher free standing time prior being immersed in coagulation is expected to solve this problem. The optimum PEI polymer concentration was found to be at 30 wt. %. At this concentration, the membrane has a dense skin layer, a sponge-like structure with uniform finger-like macrovoid at the sub-layer. The produced membrane has CO2 permeance of 500.2 GPU with selectivity of 1.43. The casting thickness effect was investigated and the optimum casting thickness is found at 300 μm. At higher casting thickness, the finger-like macrovoid is minimal with a thick skin layer of 16.84 μm. The utilization of soft coagulant such as isopropanol leads to delay demixing with thick skin layer and almost complete sponge-like structure. This membrane gives CO2 permeance of 5.49 GPU and a CO2/N2 selectivity of 11.44. Also, coagulant bath temperature was used to study condition of coagulant that could favour higher CO2 selectivity. At lower coagulation bath temperature of 0 ⁰C, the membrane structure has a complete spongy-like structure with a thickness of approximately 88.06 μm. The lower coagulation bath temperature favours the membrane separation in this condition with CO2 permeancce of 3.41 GPU and selectivity of 18.94. Meanwhile, there is development of finger-like macrovoid at higher coagulation bath temperature of 30 ⁰C upward with increasing thickness of the membrane. However, PEI membranes with a free standing time (FST) prior immersion into coagulation bath improved the CO2 separation performance. These membranes at 30 min (FST) showed CO2 permeance of 3.35 GPU combined with a CO2/N2 selectivity of 29.79. These membranes were found to acquire good control in producing the PEI membrane for CO2 separation. Generally, the overall results showed the PEI membrane is able to producegood selectivity compared to other polymer for CO2 separation. It can be concluded that the PEI membrane is comparable for CO2 separation with good selectivity.